Pengaruh Budaya Kerja dan Kompensasi terhadap Kinerja Karyawan pada PT. Pulau Nusantara Indonesia - Fitria Fandalisah; Iswat Iswat; Anis Fitriyasari (Journal Economic Excellence Ibnu Sina, 2025)
The purpose of this study is to determine the impact of work culture and imbalance on employee performance at PT. Pulau Nusantara Indonesia. In the era of global competition, human resources play a vital role in determining a company's competitiveness in facing market dynamics. Based on the results of the Key Performance Indicator (KPI) survey, most employees fall into category B, indicating that their performance has not yet reached the company's optimal standards. This condition is strongly suspected to be influenced by several factors, including a work culture that does not support innovation, high workloads, and an imbalanced system that does not provide adequate work satisfaction and motivation. This study uses a quantitative approach involving 35 permanent employee respondents at PT. Pulau Nusantara Indonesia, selected using a saturated sampling method. Data were collected through literature studies, direct field observations, and the distribution of Likert-based questionnaires. Furthermore, the data were analyzed using multiple linear regression methods to determine the extent of influence of each independent variable on the dependent variable. The results of the analysis indicate that both work culture and the imbalance system have a positive and significant influence on employee performance, both partially and simultaneously. Based on these findings, management is advised to build a collaborative and adaptive work culture and review structural imbalances to align with employee expectations and the company's vision. These efforts are believed to sustainably increase employee productivity and loyalty. Based on these findings, management is advised to build a collaborative and adaptive work culture and review structural imbalances to align with employee expectations and the company's vision.